The future of evaluation of lower secondary schools’ management - Chodakowska, Ewa (Business, Management and Economics Engineering, 2015)
Efficiency of educational institutions is a significant issue worldwide. However, there is no commonly accepted way to measure the quality of management of education services. Mainly because it too much depends on the national factors: political, economic or legal. Moreover, it has been proved that the efficiency of the school’s teaching is affected directly by the environmental factor represented by selected characteristics of students. Therefore, taking into account value-added students’ knowledge rather than absolute exam results changes evaluation of the schools’ efficiency. The article contribute in international discussions about future of evaluation the quality of management in educational sector. In the article the model of evaluation Polish lower secondary schools’ management taking into account local and environmental context is proposed. On the basis of Bialystok’s schools, author shows that the implementation of DEA could be useful and provides additional knowledge about the efficiency of management in educational institutions.